TEMPORAL AND SPATIAL RECORDS OF ACTIVE ARC-CONTINENT COLLISION IN TAIWAN: A SYNTHESIS - Huang C.-Y.; Yuan P.B.; Tsao S.-J. (My University, 2006)
Well-documented stratigraphy and clearly defined geodynamics in Taiwan, where some of the best records on arc-continent collision have been preserved, offer a unique example for the study of collision belts worldwide. The oblique arc-continent collision in Taiwan caused a simultaneous and sequential migration of four tectonic processes. Beginning from 16 to 15 Ma, subduction of the South China Sea oceanic crust beneath the Philippine Sea plate resulted in volcanism in the Coastal Range and formation of an accretionary prism in the Central Range. Beginning in the latest Miocene-earliest Pliocene, the subduction was followed by initial arc-continent collision, as supported by the following: unroofing and erosion of the deformed accretionary prism, and deposition of sediments thus derived in the adjacent accretionary forearc (5 Ma) and slope basins (4 Ma); waning of volcanism (north, 6-5 Ma; south, 3.3 Ma); buildup of fringing reefs on the gradually quiescent volcanoes (north, 5.2 Ma; south, 2.9 Ma); arc subsidence by strike-slip faulting and the development of pull-apart intra-arc basins (north, 5.2-3.5 Ma; south, 2.9-1.8 Ma); thrusting of forearc sequences to generate a collision complex starting from 3 Ma; and clockwise rotation of the arc-forearc sequences (north, 2.1-1.7 Ma; south, 1.4 Ma). The collision propagated southward and reached southern Taiwan by 5 Ma, as evidenced by the successive deformation of the associated accretionary wedge en route. Afterward, the advanced arc-continent collision stage appeared in the earliest Pleistocene, as marked by the westward thrusting and certain of the Luzon arc-forearc against the accretionary wedge (north, 1.5 Ma; south, 1.1 Ma) and exhumation of the underthrust Eurasian continent rocks (north, 2.0-1.0 Ma; south 1.0-0.5 Ma). The final stage of the tectonic process, arc collapse-subduction, began by 1 Ma off the northern Coastal Range. The geologic records compiled and presented in this study strongly support the scenario of a continous southward migration of tectonic processes and a change in sediment source and structural style. Most importantly, the model has a broad potential for reconstructing and predicting the evolution of arc-continent collision through space and time. © 2006 Geological Society of America.
Keywords: ARC-CONTINENT COLLISION; COLLISION SUTURE; OBLIQUE COLLISION; STRATIGRAPHIC RECORDS; TAIWAN; Pleistocene; Pliocene; Miocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен